2014
DOI: 10.1007/s11029-014-9453-8
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Structure and Adhesive Properties of Epoxy-Silicate Composites

Abstract: Compositions based on an ED-20 resin with three types of modifiers: natural montmorillonite (MMT)Cloisite Na + , organomodified MMT Cloisite 30B, and halloysite, were investigated. An optimum regime was chosen for preparation of the epoxy/modifier systems by employing the ultrasonic mixing. The rheological characteristics of suspensions were used to estimate the distribution of modifier in the epoxy oligomer. According to rheological data, the best dispersion of MMT in the epoxy oligomer after ultrasonic stirr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The addition of both MMT and HNT improved the mechanical properties, however, MMT‐containing nanocomposites showed better results for moduli and water barrier properties while HNT promoted an enhancement on elongation at break. Brantseva et al have studied epoxy/clay composites with natural MMT, an organically modified MMT and halloysite nanotubes. They have found that the best dispersion was obtained for the organically modified clay.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of both MMT and HNT improved the mechanical properties, however, MMT‐containing nanocomposites showed better results for moduli and water barrier properties while HNT promoted an enhancement on elongation at break. Brantseva et al have studied epoxy/clay composites with natural MMT, an organically modified MMT and halloysite nanotubes. They have found that the best dispersion was obtained for the organically modified clay.…”
Section: Introductionmentioning
confidence: 99%
“…Epoxy resins are among the important thermoset polymers with their mechanical, thermal, and chemical properties . They have been widely investigated in the scientific area and various industries because of high mechanical strength, low shrinkage, outstanding resistance to corrosion and chemicals, good adhesion performance, and electrical properties . In spite of the known benefits of epoxy resins, they are brittle and flammable materials , so suitable fillers including clay, organic, and inorganic materials like fly ash, copper slag, and so forth are used to overcome these deficiencies.…”
Section: Introductionmentioning
confidence: 99%